Sexual violence as a predictor of unintended pregnancy among married young women: evidence from the 2016 Nepal demographic and health survey - Acharya, Kiran (BMC Pregnancy Childbirth, 2019)
BACKGROUND: Sexual violence in marital relationship is higher among women married at young age. Although sexual violence has been found to increase risk for unintended pregnancy, there is a limited published data from Nepal linking sexual violence with unintended pregnancy. The current study aimed to investigate association of partner sexual violence with unintended pregnancy among young married women who experienced child birth in last 5 years. METHODS: Using data from Nepal Demographic and Health Survey, we studied the prevalence of sexual violence and unintended pregnancy, and their association among 560 married women (weighted sample) of 15–24 years who gave childbirth in last 5 years of the survey. We used multivariate logistic regression to analyse the association of sexual violence and other factors with unintended pregnancy. Analysis was conducted considering inverse probability weighting, clustering, and stratification to provide unbiased estimates of the population parameters. RESULTS: Nearly a quarter of women (22.7%) reported to have experienced unintended pregnancy in the last 5 years of the survey and almost one in 10 women (9%) reported to have ever experienced sexual violence from their husbands. Women who ever experienced sexual violence from their husbands were at 2.3 times higher odds to report an unintended pregnancy (aOR = 2.3; 95% CI = 1.1–4.8) compared to women who did not experience sexual violence from their husbands independent of important socio-demographic variables and ever use of contraception. CONCLUSION: The strong association of sexual violence within marital relationship with unintended pregnancy among young women in Nepal necessitates the provision of comprehensive sexual and reproductive health services. Women need routine assessment, and referral to appropriate services for sexual violence to reduce unintended pregnancy and its consequences.